Dissecting the mid-infrared heart of M83 with JWST - Hernandez, Svea; Jones, Logan; Smith, Linda J.; Togi, Aditya; Aloisi, Alessandra; Blair, William P.; Hirschauer, Alec S.; Hunt, Leslie K.; James, Bethan L.; Kumari, Nimisha; Lebouteiller, Vianney; Mingozzi, Matilde; et al. (The astrophysical journal, 2023)
We present a first look at the MRS observations of the nucleus of the nearby galaxy M83, taken with MIRI on board JWST. The observations show a rich set of emission features from the ionized gas, warm molecular gas, and dust. To begin dissecting the complex processes in this part of the galaxy, we divide the observations into four different regions. We find that the strength of the emission features varies strongly from region to region, with the southeast region displaying the weakest features tracing the dust continuum and interstellar medium (ISM) properties. Comparison between the cold molecular gas traced by the 12CO (1-0) transition with the Atacama Large Millimeter/submillimeter Array and the H2 S(1) transition shows a similar spatial distribution. This is in contrast to the distribution of the much warmer H2 emission from the S(7) transition found to be concentrated around the optical nucleus. We use the rotational emission lines and model the H2 excitation to estimate a total molecular gas mass accounting for the warm H2 component of M(>50 K) = 67.90 (±5.43) × 106 M ⊙. We compare this value to the total gas mass inferred by probing the cold H2 gas through the 12CO (1-0) emission, M(CO) = 17.15 × 106 M ⊙. We estimate that ∼75% of the total molecular gas mass is contained in the warm H2 component. We also identify [O iv] 25.89 μm and [Fe ii] 25.99 μm emission. We propose that the diffuse [Fe ii] 25.99 μm emission might be tracing shocks created during the interactions between the hot wind produced by the starburst and the much cooler ISM above the galactic plane. More detailed studies are needed to confirm such a scenario.
Veröffentlicht: 16. Mai 2023
Gesehen am 26.07.2023